Production and Characterization of Chitosan-Based Magnetic Field-Sensitive Beads: A Comprehensive Study on Synthesis, Structural Properties, and Environmental Applications - Taşar, Şeyda; İpek, Ömer; Duranay, Neslihan (My University, 2025)
The primary objective of this study was to synthesize chitosan-based magnetic bead sorbents (MCS) and evaluate their effectiveness in the sorption of both organic solvents and distilled water. In the initial phase, chitosan-based polymeric beads were synthesized using the precipitation-aggregation method, followed by comprehensive characterization using appropriate instrumental and analytical techniques to determine their physical and chemical properties. An interesting observation in this study was that the MCS without any cross-linking agents displayed a significantly higher capacity for distilled water sorption compared to those cross-linked with glutaraldehyde or epichlorohydrin. The study revealed that non-cross-linked chitosan beads exhibited the highest sorption capacity for distilled water (35%), while cross-linked beads showed a reduced capacity of (24%). On the other hand, cross-linking benefited the sorption of organic solvents, particularly toluene. The beads cross-linked with glutaraldehyde exhibited slightly better toluene sorption capacity than those cross-linked with epichlorohydrin, which might be attributed to differences in the molecular interactions between the cross-linkers and the solvent molecules. For organic solvents, glutaraldehyde-cross-linked beads achieved the highest toluene sorption (27%), slightly outperforming epichlorohydrin-cross-linked beads (25%). Furthermore, the study found that temperature played a crucial role in influencing the sorption capacity of the MCS. The sorption capacity decreased by approximately 15% as the temperature increased from 25 °C to 45 °C, highlighting the temperature-dependent nature of the process. This inverse relationship between temperature and sorption capacity could be due to the reduced interaction between the solvent molecules and the surface of the MCS at higher temperatures, potentially caused by increased molecular motion that hinders effective adsorption. These findings provide valuable insights into the design of chitosan-based magnetic sorbents for different applications, particularly in removing organic solvents and water purification processes. Future studies could further explore the optimization of cross-linking agents and investigate these sorbents' long-term reusability and stability in various environmental conditions.
Keywords: Chitosan; characterization; magnetic bead; sorption properties